Pengaruh Konformasi Butt Shape terhadap Karakteristik Karkas Sapi Brahman Cross pada Beberapa Klasifikasi Jenis Kelamin - Harapin Hafid H; R Priyanto (Faculty of Animal Science, Bogor Agricultural University, 2006)
Domestic demand on beef is increasing today. However the beef supply can not fulfil the demand so that importation of beef and feeder cattle is still required. Beef cattle feedloting is now growing in Indonesia. This research was done to study the growth and development of carcass components of beef carcas from Brahman Cross cattle. The number of animals used was 165 heads with the body weight range 350 - 400 kg taken from feedlot fattening. The experiment was set in completely randomized factorial design withh two factors, namely butt shape conformation (butt shape score D, C, B) and sex class (heifer, steer, cow). Parameter of carcass characteristic, i.e. carcass weight, carcass percentage, loin eye area, fat thickness of ribs 12th, fat percentage of kidney, pelvic and hearth, and fat thickness of rump P8.The result of this study showed that the increase of butt shape conformation score significantly increased loin eye area, especially in heifer and cow sex class. Key words: butt shape conformation, carcass characteristic, Brahman cross cattle, sex class